At the rhythm of community: teaching and learning among Galibi- Marworno indigenous children - Tassinari, Antonella (2015)
The article is based on field research conducted by the authorsamong Galibi-Marworno people from Uaçá region, at northern state of Amapa, Brazil. The objective is to present some aspects of their pedagogy, which is founded on the importance of freedom and autonomy for an accurate learning and the production of healthy bodies, focusing on nonverbal aspects of learning, the creativity of imitation and the children agency involved in those processes. The article presents the Galibi-Marworno’s ideas about childhood and child development and their strategies in the transmission of knowledge, contextualizing them in relation to the history and organization of the people. This description of the Galibi-Marworno’s learning processes aims to contribute to a more respectful schooling process, as required by Brazilian law.